2009
DOI: 10.1139/x09-054
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal differentiation in growth and phenology among populations of temperate-zone tree species growing in a common garden

Abstract: The aim of the study was to determine whether there are genetic variations in growth and leaf phenology (flushing and senescence) among populations of six woody species ( Abies alba Mill., Acer pseudoplatanus L., Fagus sylvatica L., Fraxinus excelsior L., Ilex aquifolium L., and Quercus petraea (Matt.) Liebl.) along altitudinal gradients, using a common-garden experiment. We found (i) significant differences in phenology and growth among provenances for most species and (ii) evidence that these among-populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
266
5
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(314 citation statements)
references
References 42 publications
34
266
5
9
Order By: Relevance
“…In addition, growing season tends to increase toward warmer low-elevation sites. Furthermore, common-garden experiments have shown that populations from high elevations have lower growth rates than populations from high altitudes (Vitasse et al 2009(Vitasse et al , 2013Montesinos-Navarro et al 2011). Similar trends were observed in our study (authors' personal observations).…”
Section: Raspravasupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, growing season tends to increase toward warmer low-elevation sites. Furthermore, common-garden experiments have shown that populations from high elevations have lower growth rates than populations from high altitudes (Vitasse et al 2009(Vitasse et al , 2013Montesinos-Navarro et al 2011). Similar trends were observed in our study (authors' personal observations).…”
Section: Raspravasupporting
confidence: 92%
“…These ecologically divergent habitats may have led to the general subdivision into two distinct ecotypes. Adaptation to local environmental conditions in the continental region probably resulted in a higher growth rate and large-leaf morphotypes which increase the species' competitive ability and long-term success, whereas in the Alpine-Dinaric region natural selection has probably favoured greater cold-tolerance (Körner 2003;Vitasse et al 2009). We also believe that our results could be valuable baseline data for the development of more efficient management plans for this boreal tree species.…”
Section: Conclusion Zaključcimentioning
confidence: 99%
“…While these temperature data effectively show overall changes across several sites, the resultant effects on native tree populations have not been thoroughly examined. The effects of changes to temperature and precipitation on tree growth and development may be positive or negative depending on site, morphological and physiological characteristics of the species' (Vitasse et al 2009, Vitasse et al 2014, Bussotti & Pollastrini 2015. On the Mediterranean island of Mallorca, Gulías et al (2009) reported correlations between meteorological variability and both growth form and environmental adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Co-and countergradient patterns witness, therefore, contrasting responses of populations to natural selection (Soularue and Kremer, 2012;Kremer et al, 2014). Indeed, oaks (Vitasse et al, 2009a) and ashes (Vitasse et al, 2009b) exhibit cogradient variations in the timing of bud burst (TBB), whereas beech and most conifers exhibit countergradient variations. It is now necessary to determine which combinations of evolutionary factors were responsible for generating these differentiation patterns when trying to predict how a species might evolve in response to current and future rapid changes in climate.…”
Section: Introductionmentioning
confidence: 99%